Nesting behavior and ecological preferences of five Diphaglossinae species (Hymenoptera, Apoidea, Colletidae) from Argentina and Chile - Sarzetti, Laura Cristina (2013)
The nests of Cadeguala albopilosa (Spinola, 1851), Diphaglossa gayi Spinola, 1851, Ptiloglossa tarsata (Friese, 1900), Ptiloglossa matutina (Schrottky, 1904) and Zikanapis tucumana (Moure, 1945) (Colletidae, Diphaglossinae) from Argentina and Chile are described herein. They show similar features to those of other Diphaglossinae: they consist of a main tunnel, cells disposed radially, isolated or in pairs, and connected to the main tunnel by laterals ones. Main tunnels are mostly vertical in species nesting in soil surface but horizontal to inclined in D. gayi, which nests in banks. Cells are vertical with curved necks. The cells of C. albopilosa show less curved necks (less than 90°), whereas in the remaining four species the cell neck is highly curved (90° or more). Cells of P. tarsata have a spiral earthen closure and a wad cottonlike material, whereas in P. matutina only had the last one. In the remaining studied species any type of closure were found. Cocoons of C. albopilosa and P. tarsata are coriaceous showing a closure composed of three disks. Zikanapis tucumana and possibly P. matutina showed dim-light foraging. The remaining species are diurnal. The climate in their nesting sites is highly diverse, ranging from 8°C to 20°C in mean annual temperature, and from 250 mm to 3000 mm in mean annual precipitation. Only C. albopilosa and, to a lesser extent, Z. tucumana nested gregariously. Zikanapis tucumana and P. tarsata were observed visiting flowers of Solanum.